Cost and scenario analysis of intermodal transportation routes from Korea to the USA : after the Panama Canal expansion - Kim, Junseung (2021)
This study is aimed at suggesting the most economical transportation route by comparing seven different Korea–US intermodal transportation routes for automotive parts exported to Southeastern USA. To keep up with the global competition of parts makers, which are expanding their markets based on advanced technology and enormous capital, Korean automotive parts makers also need to actively advance their markets overseas. From this point of view, selecting an efficient transport route and transportation modes for overseas export is essential. To this end, the most efficient transportation route from the perspective of total logistics cost was selected by adapting the inventory-theoretic model, using information such as the logistics status of a specific company and the logistics freight rates and transit time for the third quarter of 2019. Thus, the scenario analysis was conducted assuming that variables—namely transportation cost per unit, commodity value, inventory cost and additional conditions such as terminal free time—were modified. Through this study, the optimal transportation route was selected by fully considering and predicting the total logistics cost component and the variability of the major factors.